EFEKTIVITAS AKTIVITAS FISIK DAN POLA MAKAN TERHADAP KECEPATAN PENGENDALIAN KADAR GULA DARAH PADA PENDERITA DM - Augustianny Situmeang; Manotar Sinaga; Hardinayanti Simamora (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2019)
The International Diabetes Federation (IDF) predicts an increase in the number of DM-based in Indonesia from 9.1 million in 2014 to 14.1 million in 2035. The Indonesian Society of Endocrinology (PERKENI) states that there are at least 4 successful pillars of diabetes mellitus, education, diet, activity and treatment. This research aims to determine the effectiveness of physical activity and diet to the speed of control of blood sugar levels in patients with DM in the work area of Sarudik Puskesmas in Central Tapanuli District 2018. The design of research used is observational research. The research population is all patients who have DM in the work area of Sarudik Puskesmas Central Tapanuli District as much as 70 respondents. Sampling technique is Purposive Sampling. The measuring instruments used are dummy tables and glucometers. Data analysis using Chi Square Test. The results showed that the majority of respondents had less physical activity of 25 people (78.1%), having a less than good diet of 27 people (84.4%) and has a poor blood sugar control rate of 28 people (87.5%). The conclusion of research is the effectiveness of physical activity and diet to the speed of blood sugar control in patients with DM in the work area of Sarudik Puskesmas in Central Tapanuli District 2018. It is suggested that respondents can follow regular physical activity and make meal arrangement in order to lower blood sugar levels.